The Wash water storage scheme symposium, 9 November 1976 (Thomas Telford, 1976)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a joint symposium with the Central Water Planning Unit held on 9 November 1976.